PENGARUH MODEL PEMBELAJARAN INQUIRY TRAINING BERBANTU MEDIA AUDIOVISUAL TERHADAP HASIL BELAJAR SISWA - Carolina Sri Athena Barus; Netti Simatupang (Jurusan Pendidikan MIPA FKIP Universitas Pattimura, 2023)
This study aims to examine how using the inquiry training learning model to support audiovisual media impacts student learning outcomes. This research was conducted at SMA N 7 Medan Pakam using the inquiry training learning model in the experimental class and conventional learning in the control class. This type of research is quasi-experimental with a two-group pretest-posttest design. The study population was all class X SMA Negeri 7 Medan students. Sampling was done by random sampling, namely class X MIPA-3 as the experimental class and class X MIPA-2 as the control class with 35 students each. The instruments used in this study consisted of (1) essay form learning (8 questions declared valid by experts) and (2) student activity sheets. Based on the research results, the average pretest score for the experimental class was 36.63. The control class was 38.31, the average posttest score for experimental class students was 68.91, and for the conventional class was 63.54. The results of hypothesis testing using the different test (t-test) obtained can be interpreted that there are significant differences due to the influence of the Inquiry Training learning model helping audiovisual media on student learning outcomes than conventional learning